Functional Relationship Between Grain Yield and Spikes Per Square Meter of Wheat as Influenced by Seed Rate Under Late Sown Condition (Bangladesh Agronomy Journal, 2020)
An experiment was conducted at Agronomy Research Field of Bangladesh Agricultural Research Institute, Gazipur for five consecutive years (2014-2015 to 2018-2019) to establish a functional relationship between grain yield and spikes/m2 of wheat at late sown condition. Variation of spikes/m2 was created by five seed rates (90, 120, 150, 180  and 210 kg/ha). Pooled average value of spikes / m2 was observed the highest (479-506) in 180-210 kg seed /ha. From the structural treatment, the highest grain yield (pooled average of 3876-4153 kg/ha ranged 3295-5028 kg/ha) of wheat was produced in the seed rate of 150-180 kg/ha. The estimated optimum seed rate was found 162.29 kg/ha with the estimated grain yield 3989 kg/ha of wheat at late sown condition through the developed function model of Y=485.91+43.17X-0.133X2 (R2=0.87). Again, the estimate optimum spikes/m2 was noticed 423 when the estimated grain yield of wheat was 4135 kg/ha at late sown condition through the developed functional model of Y=-2837+32.98X-0.039X2 (R2=0.83). The grain yield would be increased about 13% as compared to recommended seed rate (120 kg/ha) of wheat. Spikes / m2 had significant positive correlation with seed rate (r=0.79 at p=0.05) of wheat. Relationship between observed grain yield and predicted grain yield (when relationship between spikes/m2 and grain yield) showed a good consistency (Y=1.0006X, R2=0.94 and r = 0.97 at p